Selection of Endemic Lactic Acid Bacteria for Lactose-Free Milk Production - Chitchyan, K. V.; Verdyan, A. A. (ՀԱԱՀ հիմնադրամ)
The β-galactosidase activity of lactic acid bacteria isolated from traditional lactic acid product matzoon was studied. It has been shown that some endemic lactic acid bacteria isolated from the matzoon samples produced from cow milk have β-galactosidase activity. Three Strains have been selected out of 370 studied lactic acid bacteria. β-galactosidase is of great practical importance and is also used for the production of glucose-galactose syrups, sweeteners, as well as for obtaining lactose-free milk and whey processing during waste disposal.
Keywords: Veterinary Science and Animal Breeding